Traces of the History of Multiculturalism in the City of Medan: Ethnic Interaction and the Formation of City Identity - Yushar Tanjung; Sinta Bella; Maretta Br Ginting; Marliana Br Sianipar; Sri Ajeng Widya Sari; Wanda Fitria (Jurnal Ragam Pengabdian, 2026)
The city of Medan is one of the major cities in Indonesia that develops in a multicultural social and cultural context. The city's ethnic diversity was formed through a long historical process influenced by colonialism, migration, and urban economic development. This study aims to examine the historical traces of multiculturalism in the city of Medan by focusing on interethnic interaction and its role in the formation of city identity. The research uses a qualitative approach with historical research methods, which include heuristic stages, source criticism, interpretation, and historiography. Data was obtained through documentation studies and literature studies on archives, historical documents, and relevant scientific works. The results of the study show that the multiculturalism of Medan City was formed since the colonial period through the migration of various ethnic groups such as Malays, Bataks, Chinese, Javanese, Tamil Indians, Minangkabau, and Arabs. Interethnic interaction takes place in the economic, social, cultural, and religious fields, which gives birth to a dynamic pattern of relations, both in the form of cooperation and social segregation. The process of cultural acculturation, especially in language, culinary, and social traditions, is an important factor in shaping the plural and inclusive identity of the City of Medan. This study concludes that multiculturalism is not only a historical heritage, but also a social capital that plays a strategic role in maintaining social cohesion and building the identity of the city of Medan as a cosmopolitan city in North Sumatra